Economic burden of chronic viral hepatitis C - R. A. Yakhina; I. A. Lakman; D. A. Valishin; R. Kh. Bakhitova (Фармакоэкономика, 2022)
Background. The spread of chronic viral hepatitis C (CVHC) among the population entails significant costs for society, both direct, associated with the treatment of such patients, and indirect, associated with the shortfall in fiscal payments to the budget, due to the disability of this category of patients. Therefore, an important task remains to assess the global economic burden of the disease, taking into account the pathological conditions of the human body associated with it.Objective: to systematize studies of published sources devoted to assessing the global economic burden of chronic viral hepatitis C.Material and methods. A feature of the proposed review design is paying attention not only to the objects of assessment under study, but also to the instrumental (including mathematical) means of scenario assessment of the global burden. The study analyzed 29 sources published between 2014 and 2020 and dedicated to assessing and forecasting the global economic burden of CVHC both in individual countries and continents as a whole, and in individual regions of countries. The main criterion for the selection of studies was the availability of an estimate of the global burden of CVHC, taking into account the use of direct antiviral drugs for the treatment of hepatitis C. The search was conducted in PubMed/MEDLINE and eLibrary databases, and in the ResearchGate network.Results. Of the 29 analyzed sources, 40% of the works consider the burden for CVHC only of certain genotypes; in the overwhelming number of articles (80%), when assessing the burden, the distribution of patients by the degree of liver fibrosis is taken into account. In 50% of the studies reviewed, quality of life adjustment tools (QALY or DALY) were used to estimate the global economic burden. A third of the publications took into account both the direct costs of treating CVHC and indirect costs, including those associated with a shortfall in the contribution to the gross national product due to temporary or permanent disability of this category of patients.Conclusion. The analysis showed that interest in assessing the global burden of CVHC began to appear in recent years, when expensive directacting antivirals for the treatment appeared. This is explained by the emergence of a question about the cost of implementing a scenario in which by a certain year it will be possible to completely exclude the spread of the disease. The results of this work may be useful in conducting such studies, including the determining of their design and the use of modern mathematical modeling tools.